2020
DOI: 10.1111/desc.13034
|View full text |Cite
|
Sign up to set email alerts
|

Early word‐learning skills: A missing link in understanding the vocabulary gap?

Abstract: Socioeconomic status (SES) has been repeatedly linked to the developmental trajectory of vocabulary acquisition in young children. However, the nature of this relationship remains underspecified. In particular, despite an extensive literature documenting young children's reliance on a host of skills and strategies to learn new words, little attention has been paid to whether and how these skills relate to measures of SES and vocabulary acquisition. To evaluate these relationships, we conducted two studies. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 97 publications
2
9
0
Order By: Relevance
“…Greater increases in beta were further associated with greater vocabulary knowledge, suggesting this neural mechanism underlies a strategy which supports both successful word learning and vocabulary. Critically, consistent with recent research, our findings suggest that poorer word learning and vocabulary outcomes among children from lower SES households are not attributed to differences in vocabulary alone, as groups did not significantly differ in vocabulary, but are rather associated with differences in the skills and strategies used to build that vocabulary (Levine et al, 2018;Shavlik et al, 2020). Some children from lower SES households are better word learners, while others are not, and these differences are related to the process of how a word is learned.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Greater increases in beta were further associated with greater vocabulary knowledge, suggesting this neural mechanism underlies a strategy which supports both successful word learning and vocabulary. Critically, consistent with recent research, our findings suggest that poorer word learning and vocabulary outcomes among children from lower SES households are not attributed to differences in vocabulary alone, as groups did not significantly differ in vocabulary, but are rather associated with differences in the skills and strategies used to build that vocabulary (Levine et al, 2018;Shavlik et al, 2020). Some children from lower SES households are better word learners, while others are not, and these differences are related to the process of how a word is learned.…”
Section: Discussionsupporting
confidence: 90%
“…Establishing a better understanding of the nature of differences in early vocabulary development, especially in a low SES population that is known to struggle disproportionately with learning new words, is critical for creating subsequent interventions which promote word learning success in children from all SES backgrounds (Shavlik et al, 2020). In the current study, we found that children who are stronger word learners engage theta and beta when learning a new word, while children who are not as strong of word learners engage more alpha.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations